UJI ANTAGONISME ISOLAT MUTAN Sclerotium rolfsii SACC. TERHADAP ISOLAT TIPE LIAR Sclerotium rolfsii SACC. DI LABORATORIUM - Nurainun Nasution; Hasanuddi Hasanuddi; Darma Bakti Darma Bakti (Universitas Sumatera Utara, 2013)
Antagonism test mutated isolate of Sclerotium rolfsii Sacc. against wild type isolate ofSclerotium rolfsii Sacc. in laboratory. This research aims to determine ability from mutated isolateof S. rolfsii to inhibit wild type isolate of S. rolfsii’s growth in laboratory. It was conducted in PlantPathology Laboratory, Faculty of Agriculture, University of Sumatra Utara, Medan from Septemberuntil November 2012. It was done by using Completely Randomized Design Non Factorial with 7treatments and 3 replications. This research’s result showed that highest percentage of inhibitingzones contained at 20 and 25 minutes UV irradiated isolate (M4 and M5) at 63.66 % and 60.95 %and the lowest were at 30 and 15 minutes UV irradiated isolate (M6 and M3) at 52.80 % and55.17 %. Macroschopic of S. rolfsii experience of the change at 15 and 30 minutes UV irradiatedisolate (M3 and M6) were in the form of colony more dense and compact, myselium like cotton andhyphae in the form of refinement. The highest diametre from mutated isolate of S. rolfsii containedat 20 minutes UV irradiated isolate (M4) at 6.63 cm and the lowest were at 30 minutes UVirradiated isolate (M6) at 4.76 cm. The highest wide of growth from mutated isolate of S. rolfsiicontained at 20 minutes UV irradiated isolate (M4) at 34.15 cm2 and the lowest were at 30 minutesUV irradiated isolate (M6) at 18.54 cm2.Keywords: S. rolfsii, antagonism, pathogenecity, sclerotia.